Captain Underpants and the preposterous plight of the purple potty people : the eighth epic novel - Pilkey, Dav. (New York : Blue Sky Press, 2006)
When George and Harold use their traveling purple potty to travel to another dimension where the school is nice and the principal, Mr. Krupp, thinks they're funny, they meet up with their evil twins and must face their cleverest enemies ever -- themselves.
Keywords: Graphic novels; School stories; Graphic novels